Synergus Hartig species group (Hymenoptera: Cynipidae: Synergini) with partially smooth mesopleurae from the New World - Lobato-Vila, Irene; Equihua-Martínez, Armando; Estrada-Venegas, Edith G.; Cibrián-Tovar, David; Barrera-Ruíz, Uriel M.; Pujade-Villar, Juli (Zootaxa, 2020)
Inquiline oak gall wasps from the genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) that occur in the New World should be classified into the following morphological groups: i) species with the radial cell of fore wings open; ii) species with the radial cell of fore wings closed and mesopleurae completely sculptured, always with transversal striae covering its surface; iii) species with the radial cell of fore wings closed and mesopleurae partially smooth, with the speculum always shiny and not sculptured. The latter group, which appears to be unique to the New World’s fauna, is the focus of this study. An exhaustive taxonomical revision of all the Synergus species within this morphological group is carried out for the first time after the initial treatment by Lobato-Vila & Pujade-Villar (2017). Redescriptions, images and new distribution and biological data are provided. A new species from Mexico, Synergus aurofacies Lobato-Vila & Pujade-Villar, sp. nov., is here formally described and illustrated. Synergus variegatus McCracken & Egbert, 1922 is a junior synonym of S. flavens McCracken & Egbert, 1922 syn. nov.; S. profusus McCracken & Egbert, 1922 is a junior synonym of S. pacificus McCracken & Egbert, 1922 syn. nov.; and S. flavus Kieffer, 1904 and S. varicolor Fullaway, 1911 are junior synonyms of S. pomiformis (Ashmead, 1885) syn. nov. A key to species of this group is provided. The morphological traits of the species with partially smooth mesopleurae are discussed.